CD101 as an indicator molecule for pathological changes at the interface of host-microbiota interactions - Wrage, Marius; Kaltwasser, Johanna; Menge, Sonja; Mattner, Jochen (International Journal of Medical Microbiology, 2021)
Intestinal microbiota signal to local and distant tissues in the body. Thus, they also regulate biochemical, metabolic and immunological processes in the gut and in the pancreas. Vice versa, eating habits or the immune system of the host shape the intraluminal microbiota. Disruptions of these versatile host-microbiota interactions underlie the pathogenesis of complex immune-mediated disorders such as inflammatory bowel disease (IBD) or type 1 diabetes (T1D). Consequently, dysbiosis and increased intestinal permeability associated with both disorders change the biology of underlying tissues, as evidenced, for example, by an altered expression of surface markers such as CD101 on immune cells located at these dynamic host-microbiota interfaces. CD101, a heavily glycosylated member of the immunoglobulin superfamiliy, is predominantly detected on myeloid cells, intraepithelial lymphocytes (IELs) and regulatory T cells (Tregs) in the gut. The expression of CD101 on both myeloid cells and T lymphocytes protects from experimental enterocolitis and T1D. The improved outcome of both diseases is associated with an anti-inflammatory cytokine profile and a reduced expansion of T cells. However, distinct bacteria suppress the expression of CD101 on myeloid cells, similar as does inflammation on T cells. Thus, the reduced CD101 expression in T1D and IBD patients might be a consequence of an altered composition of the intestinal microbiota, enhanced bacterial translocation and a subsequent primining of local and systemic inflammatory immune responses.
CRIS-Team Scopus Importer:2021-04-09
Keywords: CD101; Host-microbe interactions; Immune-mediated disease; Microbiota; Mucosal surfaces